Respiratory consultations in asthmatic compared with non-asthmatic children in general practice. Issue 6487 (6th July 1985) - Levy, M; Parmar, M; Coetzee, D; Duffy, S W
Abstract : In a retrospective study we found that before a diagnosis of asthma had been made children with asthma had consulted their general practitioner more often with respiratory symptoms than children who were non-asthmatic under the age of four. In the second, third, and fourth years the number of consultations differed significantly between the two groups. Asthma should be suspected in any child who presents often with respiratory symptoms. This should lead to earlier diagnosis in most cases.